Effect of high temperature on the production of 2n pollen grains in diploid roses and obtaining tetraploids via unilateral polyploidization. Issue 3 (11th May 2015) - Crespel, Laurent; Le Bras, Camille; Relion, Daniel; Roman, Hanaé; Morel, Philippe; Debener, T.
Abstract To integrate the gene pool of a wild species (primarily diploid) into a cultivated pool (primarily tetraploid), a crossing between a dihaploid cultivated rose and a hybrid of Rosa wichurana allowed to obtain interspecific diploid hybrids that produced 2n pollen grains. A return to a tetraploid level sought by breeders can then be considered using sexual polyploidization, obtained by crossing a tetraploid cultivated rose with these hybrids. Application of a high‐temperature regime led to a small but significant increase in the percentage of 2n pollen grains in these hybrids of up to 4.6%. This result was obtained by applying high temperatures close to 32°C during the day to plants cultivated in a glasshouse during recurrent cycles of bloom. Crosses were made between an unreleased tetraploid hybrid tea rose, as a female, and the diploid hybrid that produces the most 2n pollen grains. Tetraploid (42.1%) and triploid (57.9%) offspring were obtained. The use of these 2n pollen grains of the first division restitution type should facilitate the introgression of complex traits of interest.